The Activities of Plant Extracts Heritage of Melayu Culture-Riau Archipelago on Bacteria Causing Diarrhea - Rodesia Mustika Roza (International Journal of Ecophysiology, 2019)
Diarrhea is one of the major health problems in Indonesia. Lingga Malay ethnic in Riau archipelago use alternative medicines in a form of a obat pahit potion to treat diarrhea. This research aimed to determine the antibacterial activity of obat pahit extraction against Escherichia coli ATCC 11775, Salmonella ATCC 14028 and Shigella flexneri ATCC 12022. Antibacterial activity can be seen with the formation of inhibitory zone using diffusion method. The extract concentration used were 100%, 75%, 50% and 25%. Based on the antibacterial activity test, the largest inhibitory zone against E. coli was found at 100% Cnestis palala extract of 8.29 mm and the smallest inhibitory zone was found at 25% traditional medicine practioner (TMP) 2 SP4 of 5.73 mm. The more over, the largest inhibitory zone to S. was found at 100% Bauhinia semibifida of 8.81 mm; and the smallest inhibitory zone was found at 50% TMP 2 SP4 of 6.30 mm. Antibacterial activity with the largest inhibitory zone against S. flexneri at 75% C. palala of 6.21 mm and the smallest inhibitory zone was found at 50% TMP 2 SP4 of 5.62 mm.